PERANCANGAN SIMULASI PADA SISTEM PEMAKSIMALAN PENGISIAN DAYA UNTUK KENDARAAN ELEKTRIK RODA DUA - Nasrullah, Muhammad Azka; Primanggani, Stevanus; Andromeda, Trias; Riyadi, Munawar Agus (Universitas Diponegoro, 2024)
Electric motorbikes and electric bicycles in Indonesia generally use 60V, 20Ah batteries with an average charging power of 200W. Charging an electric two-wheeler at home offers great convenience and cost-effectiveness. However, increasing charging power poses challenges due to the use of household electricity loads and limited electricity capacity, which has the potential to cause tripping. Household electricity consumption fluctuates between peak and off-peak load periods offering opportunities for optimal charging during off-peak times. This research aims to adjust the charging power of two-wheeled electric vehicles to the maximum based on household power limits. The proposed charging system design includes an AC-DC converter and a buck type DC-DC converter. This converter regulates charging power according to variations in household electrical load and limited electrical capacity. Simulation results show that two-wheeled electric vehicles can be charged at 825W, four times the average charging power, during off-peak periods thereby speeding up charging. Meanwhile, during peak load periods, the charging power is reduced to 341W to avoid tripping which disrupts household electricity use. This charging system ensures short charging and efficient use of available household electrical power while maintaining the stability of the electrical system.